50 Hz X‐Ray Diffraction Stress Analysis and Numerical Process Simulation at Laser Surface Line Hardening of Web Structures. Issue 11 (17th March 2021) - Kiefer, Dominik; Lang, Florian; Simon, Nicola; Beckmann, Felix; Wilde, Fabian; Gibmeier, Jens
Abstract : In situ synchrotron X‐ray diffraction experiments were carried out during laser surface line hardening of the common tempering steel AISI 4140 at beamline P05@PETRA III operated by Helmholtz‐Zentrum Geesthacht at the Deutsches Elektronen Synchrotron, Hamburg, Germany. A unique process chamber was used to investigate the phase and transverse surface stress evolution during a laser line hardening processes. Synchrotron radiation, in combination with microstrip line detectors, allows for a time resolution of 50 Hz. Specimen geometries were hardened using a high‐power diode laser under control of the surface temperature and constant laser beam feed. Herein, it is focused on web‐structured specimens in contrast to a flat geometry. The experimental results are discussed with regard to the workpiece geometry effect of the web structure dimensions on the temporal and spatial stress evolution. In addition, numerical process simulations based on the finite element method were carried out to support the drawn conclusions. The presented model is able to predict the surface transverse stresses inside the process zone center, while providing further 3D information. A heat build‐up in the web leads to a wider and deeper process zone, however, the absolute hardness increase and the transverse residual stresses at the surface center are not affected. Abstract : With recent developments, laser surface hardening attracted an increased interest. Herein, real‐time stress evaluation at laser surface line hardening using in situ synchrotron X‐ray diffraction with focus on the effect of specimen geometry are presented. Corresponding numerical process simulations are carried out to support the experimental findings concerning heat build‐up and the effect on residual stresses in web structures.